Psychological readiness to return to competitive sport following injury: A qualitative study - Podlog, L.; Banham, S. M.; Wadey, R.; Hannon, J. C. (The Sport Psychologist, 2015)
The purpose of this study was to examine athlete experiences and understandings of psychological readiness to return to sport following a serious injury. A focus group and follow-up semistructured interviews were conducted with seven English athletes representing a variety of sports. Three key attributes of readiness were identified including: (a) confidence in returning to sport; (b) realistic expectations of one`s sporting capabilities; and (c) motivation to regain previous performance standards. Numerous precursors such as trust in rehabilitation providers, accepting postinjury limitations, and feeling wanted by significant others were articulated. Results indicate that psychological readiness is a dynamic, psychosocial process comprised of three dimensions that increase athletes` perceived likelihood of a successful return to sport following injury. Findings are discussed in relation to previous research and practical implications are offered.